Differentiating sibling species of Zeugodacus caudatus (Insecta: Tephritidae) by complete mitochondrial genome - Yong, Hoi Sen; Song, Sze Looi; Lim, Phaik Eem; Eamsobhana, Praphathip; Suana, I. Wayan (Kluwer (now part of Springer), 2016)
Zeugodacus caudatus is a pest of pumpkin flowers. It has a Palearctic and Oriental distribution. We report here the complete mitochondrial genome of the Malaysian and Indonesian samples of Z. caudatus determined by next-generation sequencing of genomic DNA and determine their taxonomic status as sibling species and phylogeny with other taxa of the genus Zeugodacus. The whole mitogenome of both samples possessed 37 genes (13 protein-coding genes—PCGs, 2 rRNA and 22 tRNA genes) and a control region. The mitogenome of the Indonesian sample (15,885Â bp) was longer than that of the Malaysian sample (15,866Â bp). In both samples, TΨC-loop was absent in trnF and DHU-loop was absent in trnS1. Molecular phylogeny based on 13 PCGs was concordant with 15 mitochondrial genes (13 PCGs and 2 rRNA genes), with the two samples of Z. caudatus forming a sister group and the genus Zeugodacus was monophyletic. The Malaysian and Indonesian samples of Z. caudatus have a genetic distance of pÂ =Â 7.8Â % based on 13 PCGs and pÂ =Â 7.0Â % based on 15 mitochondrial genes, indicating status of sibling species. They are proposed to be accorded specific status as members of a species complex.